Corporate Tax Avoidance and Industry Concentration - Julien Martin; Mathieu Parenti; Farid Toubal (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper argues that tax avoidance by large corporations has contributed to the 25% increase in concentration among U.S. firms since the mid-1990s. Corporate tax avoidance gives large firms a competitive edge, which translates into larger market shares and an increase in the granularity of the economy. We develop IV and difference-in-differences strategies that show the causal impact of tax avoidance on firm-level sales. Had firms not resorted to tax avoidance in 2017, our results imply that the average industry concentration would have been 8.3% lower, which is around its early 2000 level.
Keywords: D22; H26; L11; D40; F23; 330; tax avoidance; industry concentration; IRS audit probability